Akame ga kill! 3 - Takahiro, 1981- (Yen Press, an imprint of Hachette Book Group, 2015)
"Tatsumi's fantasy of leading a righteous assassin's life is brutally shattered when Sheele is lost in battle. But though Tatsumi resolves to stand tall against his sorrows, a new group of Teigu Wielders appears before him: the Three Beasts!! In the battle between Teigu, where there can be only one victor, who will fall prey to death?!" --